Optical and near-infrared photometry of 94 type II supernovae from the Carnegie Supernova Project - Anderson, J. P. (2024)
Context. Type II supernovae (SNe II) mark the endpoint in the lives of hydrogen-rich massive stars. Their large explosion energies and luminosities allow us to measure distances, metallicities, and star formation rates into the distant Universe. To fully exploit their use in answering different astrophysical problems, high-quality low-redshift data sets are required. Such samples are vital to understand the physics of SNe II, but also to serve as calibrators for distinct – and often lower-quality – samples. Aims. We present uBgVri optical and Y JH near-infrared (NIR) photometry for 94 low-redshift SNe II observed by the Carnegie Supernova Project (CSP). A total of 9817 optical and 1872 NIR photometric data points are released, leading to a sample of high-quality SN II light curves during the first ∼150 days post explosion on a well-calibrated photometric system. Methods. The sample is presented and its properties are analysed and discussed through comparison to literature events. We also focus on individual SNe II as examples of classically defined subtypes and outlier objects. Making a cut in the plateau decline rate of our sample (s2), a new subsample of fast-declining SNe II is presented. Results. The sample has a median redshift of 0.015, with the nearest event at 0.001 and the most distant at 0.07. At optical wavelengths (V), the sample has a median cadence of 4.7 days over the course of a median coverage of 80 days. In the NIR (J), the median cadence is 7.2 days over the course of 59 days. The fast-declining subsample is more luminous than the full sample and shows shorter plateau phases. Of the nonstandard SNe II highlighted, SN 2009A particularly stands out with a steeply declining then rising light curve, together with what appears to be two superimposed P-Cygni profiles of Hα in its spectra. We outline the significant utility of these data, and finally provide an outlook of future SN II science.